Living well with kidney disease by patient and care partner empowerment: kidney health for everyone, everywhere - Kalantar-Zadeh, Kamyar; Li, Philip Kam-Tao; Tantisattamo, Ekamol; Kumaraswami, Latha; Liakopoulos, Vassilios; Lui, Siu-Fai; Ulasi, Ifeoma; Andreoli, Sharon; Balducci, Alessandro; Dupuis, Sophie; Harris, Tess; Hradsky, Anne; et al. (African Journal of Nephrology, 2021)
Living with chronic kidney disease (CKD) is associated with hardships for patients and their care-partners. Empowering patients and their care-partners, including family members or friends involved in their care, may help minimize the burden and consequences of CKD related symptoms to enable life participation. There is a need to broaden the focus on living well with kidney disease and re-engagement in life, including an emphasis on patients being in control. The World Kidney Day (WKD) Joint Steering Committee has declared 2021 the year of "Living Well with Kidney Disease" in an effort to increase education and awareness on the important goal of patient empowerment and life participation. This calls for the development and implementation of validated patient-reported outcome measures to assess and address areas of life participation in routine care. It could be supported by regulatory agencies as a metric for quality care or to support labelling claims for medicines and devices. Funding agencies could establish targeted calls for research that address the priorities of patients. Patients with kidney disease and their care-partners should feel supported to live well through concerted efforts by kidney care communities including during pandemics. In the overall wellness program for kidney disease patients, the need for prevention should be reiterated. Early detection with a prolonged course of wellness despite kidney disease, after effective secondary and tertiary prevention programs, should be promoted. WKD 2021 continues to call for increased awareness of the importance of preventive measures throughout populations, professionals, and policy makers, applicable to both developed and developing countries.